China fictions/English language : literary essays in diaspora, memory, story - Lee, A. Robert, 1941- (Text (Rodopi (Firm)) ;, 2008)
The world is anything but unfamiliar with diaspora: Jewish, African, Armenian, Roma-Gipsy, Filipino/a, Tamil, Irish or Italian, even Japanese. But few have carried so global a resonance as that of China. What, then, of literary-cultural expression, the huge body of fiction which has addressed itself to that plurality of lives and geographies and which has come to be known as?After China?? This collection of essays offers bearings on those written in English, and in which both memory and story are central, spanning the USA to Australia, Canada to the UK, Hong Kong to Singapore, with yet others of more transnational nature. This collection open with a reprise of woman-authored Chinese American fiction using Maxine Hong Kingston and Amy Tan as departure points. In turn follow readings of the oeuvres of Tan and Frank Chin. A comparative essay takes up novels by Canadian, American and Australian authors from the perspective of migrancy as fracture. Chinese Canada comes into view in accounts of SKY Lee, Wayson Choy, Evelyn Lau and Larissa Lai. Australia under Chinese literary auspices is given a comparative mapping through the fiction of Brian Castro and Ouyang Yu. The English language?China fiction? of Singapore and Hong Kong is located in essays centred, respectively, on Martin Booth and Po Wah Lam, and Hwee Hwee Tan and Colin Cheong. The collection rounds out with portraits of Timothy Mo as British transnational author, a selection of contextual Chinese British stories and art, and the phenomenon of?Chinese Chick Lit? novels. China Fictions/English Language will be of interest to readers drawn both to?After China? as diasporic literary heritage and comparative literature in general.